A multifunctional magnetic core–shell fibrous silica sensing probe for highly sensitive detection and removal of Zn2+ from aqueous solution1. Issue 18 (14th May 2015) - Sun, Zebin; Li, Haizhen; Guo, Dan; Sun, Jian; Cui, Guijia; Liu, Yan; Tian, Yaxi; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> A multifunctional core-shell magnetic fibrous silica sensing probe AQ-Fe3O4@SiO2@KCC-1 was prepared for the detection, adsorption and removal of Zn2+ in aqueous solution.